Daily meteorological data from automatic weather station Lions Rump, King George Island, during 2018-2023 - Joanna Plenzler (PANGAEA, 2024)
Presented dataset contains meteorological data Lions Rump automatic weather station located at 23 m a.s.l. at western shore of King George Bay (King George Island, West Antarctica) during 2018.11.02 – 2023.12.31. The dataset contains daily mean, maximum and minimum values of air temperature [°C], relative air humidity [%], wind speed [m/s] and daily sum of solar radiation [MJ/m2]. Mean values of air temperature and humidity and wind speed were calculated from measurements taken every 10 minutes. Non-processed data were used for identification of extreme values. Daily sum of solar radiation were calculated from solar radiation intensity measured every 10 minutes. Automatic weather station has a data logger manufactured by Campbell with following sensors: Vaisala temperature and humidity probe, Setra barometer, Gill Wind Sonic anemometer and Apogee pyranometer. Presented data may serve as a background for other research projects conducted at King George Island as well as an analyse of meteorological conditions itself. They could also be useful in evaluation of management plans of Antarctic Special Protected Areas located at King George Island.